2015
DOI: 10.1039/c5ay00761e
|View full text |Cite
|
Sign up to set email alerts
|

In situ studies into the characterisation and degradation of blue ballpoint inks by diffuse reflectance visible spectroscopy

Abstract: blue ballpoint inks sourced from Western Australian retailers were deposited onto commercial copy paper and analysed using diffuse reflectance visible spectroscopy. Principal component analysis showed that while several pens were clearly distinguishable based on their visible spectra alone, others exhibited overlap. Linear discriminant analysis was then used to build a chemometric model for the classification of the inks. Using a separate validation set, 71.7% of spectra were correctly assigned to a specific p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…All data pre-processing and analysis was performed using the Unscrambler® X 10.4 soware (Camo Soware AS, Oslo, Norway). Previous work investigated the use of the Kubelka-Munk (K-M) conversion, 28 as this is routinely applied to reectance spectra in order to facilitate quantitative analysis. 32,33 However, it was found that the K-M function did not improve overall discrimination, and so this function was omitted in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…All data pre-processing and analysis was performed using the Unscrambler® X 10.4 soware (Camo Soware AS, Oslo, Norway). Previous work investigated the use of the Kubelka-Munk (K-M) conversion, 28 as this is routinely applied to reectance spectra in order to facilitate quantitative analysis. 32,33 However, it was found that the K-M function did not improve overall discrimination, and so this function was omitted in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…† The deposits were then le to age in three locations representative of typical office environments as per below, with spectra previously recorded at various intervals up until two months. 28 The present manuscript is a continuation of that study utilising the same ink deposits, with additional spectra recorded at 4, 6, 8, 10, 13, 14, 19, 24, 28 and 32 months aer ink deposition.…”
Section: Sample Collection and Preparationmentioning
confidence: 95%
See 3 more Smart Citations